Putting the making in place-making: the role of traditional crafts skills and community-led conservation in the re-framing of historic environment services - Alexander Langlands (Studia Vernacula, 2024)
As Europe confronts a polycrisis of transitioning energy supplies, food sovereignty, climate change, and threats to national securities, it would be easy to lose sight of heritage as an essential component within the cultural fabric of communities. Yet as both a tangible and intangible process heritage is indispensable in offering a forward-looking resilient future for communities at the local level. This paper explores the case of Wales in light of cuts to government funding for heritage and historic environment services. It examines what changing definitions of heritage mean for how it is delivered and interrogates how notions of ‘community’ can be critiqued to extract workable co-production solutions for the sustainable conservation of built heritage assets. The case is made for a re-framing of state-led heritage delivery to better address the ambitions of the Wellbeing of Future Generations (Wales) Act 2015 with practical, participatory craft ‘hands-on’ heritage as a key element.